Correlation of biochemical profile at admission with severity and outcome of COVID-19. Issue 6 (2nd November 2021) - Sadiq, Abdullah; Khurram, Muhammad; Malik, Javaria; Chaudhary, Noman Ahmed; Khan, Muhammad Mujeeb; Yasmeen, Tahira; Bhatti, Hamza Waqar
ABSTRACT: Background: COVID-19 was detected in China in December 2019. The rapid dissemination and novelty of the disease resulted in an epidemic. This study aimed to identify biochemical parameters at admission that can be used to categorize severity and outcome of COVID −19 infection. Materials and Methods: This cross-sectional study was conducted at Allied Hospitals of RMU from April 2020 to July 2020. It included 128 randomly selected confirmed COVID-19 patients. At admission, biochemical profile (total bilirubin, alanine aminotransferases ALT, aspartate aminotransferases AST, urea, creatinine, uric acid, sodium, potassium, and chloride were correlated with severity and outcome of COVID-19 by employing t-tests and ANOVA where required. Cut-off values to predict disease severity and outcome were calculated using ROC curve. Results: The study comprised 46.1% non-severe, 29.7% severe, and 24.2% critical COVID-19 patients. 84.4% patients improved and 15.6% expired. Urea was increased in critical disease patients (p < 0.000). Higher ALT (p 0.030) and AST (p 0.004) levels were noted in severe and critical disease. Sodium (p 0.001) and chloride (p 0.026) were decreased in critical disease. Patients who expired had increased urea (p 0.000), ALT (p 0.040) and AST (p 0.002). At admission, urea >42.7 mg (sensitivity of 64.7%, specificity of 87.5%), AST >43.5 IU/L (64% sensitivity, 60% specificity), and sodium <136.9 mmol/L (sensitivity of 70.6%, specificity of 71.2%) predicted critical COVID-19 infection. Conclusion: At admission, increased urea, AST, and ALT along with decreased sodium can help in identifying COVID-19 patients with severe illness and poor outcome.